Esterificação e transesterificação simultâneas de óleo de Jatropha curcas L. utilizando o catalisador zircônia sulfatada - Raia, Rodrigo Zunta (2014)
In this study sulfated zirconia catalyst was sintethesized to promove simultaneous esterification and transesterification reaction from Jatropha curcas L. crude oil. The physicochemical oil characterization shows that the fatty acids composition has mainly oleic acid (41.71%), linoleic acid (36.42%) and an acidity of 13.99 ± 0.04 mg KOH g-1 (7.03% in oleic acid). The zirconium hydroxide synthesis was made ranging up pH of precipitation of sol-gel solution for 6, 7 and 8; after was made sulfation process using 0.5 mol L-1 sulfuric acid solution and finally was made the matter calcination using muffle. Also did the synthesizing of zirconium oxide sample using simple calcination of precursor material to show the influence of synthesis method at sample characteristics. Analyses of X-ray diffraction shows that, at sulfated zirconia the intensity of tetragonal phases is directly connected to final pH of synthesis from sol-gel solution in zirconium hydroxide such the sample synthesized using higher pH (SZ8) has higher intensity of tetragonal phase (86.94%) comparing to synthetized samples with lower pHs: SZ7 (78.67%) and SZ6 (66.01%). The N2 physisorption analyses show that the sample SZ8 has 65.81 m2 g-1 BET surface area, biggest than the all analyzed samples. The technique used shows also that, pH of synthesis variation have a light influence on pore size distribution; therefore, all samples have mesoporous characteristics. The TPD-NH3 analyses show that have an interrelationship between intensity of tetragonal crystalline phase and total acidity of sulfated samples, whereas, the total acidity is proportional to the percentage of tetragonal phase. The FTIR analysis shows that all samples have characteristics bands between 3000-3600 cm-1 for hydration and 500-750 cm-1for Zr-O connection. In addition, bands of 1000-1400 cm-1 are assigned of sulfur presence in sulfated zirconia. The catalytic tests showed that acidity of catalyst affects the ethyl esters yield for the Jatropha curcas L. oil simultaneous esterification and transesterification reaction, whereas, ethyl esters yield to SZ8 (59.4%), SZ7 (43.7%) and SZ6 (37.4%) samples were higher than non-catalytic reaction (29.7%) with ethyl esters yield. The results of the esterification of oleic acid and transesterification of neutralized Jatropha curcas L. oil also proof the influence of acidity catalyst on ethyl esters yield comparing to catalytic esterification (81.3%), non-catalytic esterification (53.1%), catalytic transesterification (48.8%) and non-catalytic transesterification (5.0%). At the catalytic tests using Jatropha curcas L. oil with different free fatty acids content, the results suggests that free fatty acids can directly influence the reaction mechanism so, esterification stage happen early and rapidly followed by triacylglyceride transesterification reaction and side reactions (thermal/catalytic cracking followed by esterification of fatty acid and hydrolysis of triglyceride and finally esterification of fatty acid), those reactions happens and induce the reaction to achieve equilibrium.